A new entomopathogenic fungus, Ophiocordyceps xifengensis sp. nov., from Liaoning, China. - Fei, Gang-Xiang; Guan, Jing-Qiang; Tian, Hui-Ling; Zhou, Ye-Ming; Qu, Jiao-Jiao; Xu, Zhongshun; Zou, Xiao (Phytotaxa, 2024)
Ophiocordyceps is an entomopathogenic fungal genus with global distribution and considerable economic implications in both biological control and biomedicine. However, the species diversity of Ophiocordyceps remains to be further investigated. In this study, a new species, Ophiocordyceps xifengensis, found parasitizing lepidopteran pupae, was discovered during a survey of insect pathogenic fungi in Xifeng County, Liaoning Province. Morphological comparative analysis revealed that this species characterized by having solitary, non-branching, woody, cylindrical asci and filamentous ascospores. Compared to its closely related species, the new species exhibits inclined embedded perithecia (0.38–0.43 mm) and smaller asci (164.8–178.9 × 7.4–10.2 μm), with its anamorphic features. Phylogenetic analysis based on multiple gene sequence data infers that Ophiocordyceps xifengensis, forming a distinct branch from other closely related species.